Lessons learned from immunological characterization of nanomaterials at the Nanotechnology Characterization Laboratory - Dobrovolskaia, Marina A. (Frontiers in Immunology, 2022)
Nanotechnology carriers have become common in pharmaceutical products because of their benefits to drug delivery, including reduced toxicities and improved efficacy of active pharmaceutical ingredients due to targeted delivery, prolonged circulation time, and controlled payload release. While available examples of reduced drug toxicity through formulation using a nanocarrier are encouraging, current data also demonstrate that nanoparticles may change a drug’s biodistribution and alter its toxicity profile. Moreover, individual components of nanoparticles and excipients commonly used in formulations are often not immunologically inert and contribute to the overall immune responses to nanotechnology-formulated products. Said immune responses may be beneficial or adverse depending on the indication, dose, dose regimen, and route of administration. Therefore, comprehensive toxicology studies are of paramount importance even when previously known drugs, components, and excipients are used in nanoformulations. Recent data also suggest that, despite decades of research directed at hiding nanocarriers from immune recognition, the immune system’s inherent property of clearing particulate materials can be leveraged to improve the therapeutic efficacy of drugs formulated using nanoparticles. Herein, I review current knowledge about nanoparticles’ interaction with the immune system and how these interactions contribute to nanotechnology-formulated drug products’ safety and efficacy through the lens of over a decade of nanoparticle characterization at the Nanotechnology Characterization Laboratory.